Optimization of The Management of Islamic Spiritual Organizations (ROHIS) as A Strategy to Improve Islamic Religious Education Learning in High Schools - Triamryaningsih, Septi; Zuliana (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This study analyzes the optimization of the management of the Islamic Spirituality Organization (Rohis) as a strategy to enhance the learning of Islamic Education at SMA Islam Al-Ulum Terpadu Medan. The main issues in PAI learning are the limited time and the overly theoretical approach. Using a mixed-methods approach, data were collected through interviews, observations, and questionnaires from 41 active Rohis students. The findings show that structured management of Rohis increased student participation by 80.5% and significantly strengthened their understanding of PAI material. Full support from the school was a key success factor, while students’ time constraints posed the main challenge. This study offers innovative strategies such as religious competitions, regular religious discussions, and the use of social media to improve the effectiveness of Rohis activities. The novelty of this research lies in the development of specific optimization steps for Rohis that can be applied in other schools, including cross-organization collaboration, the provision of dedicated spaces, and the integration of Islamic values practically in student activities.